Grease Trail Storytelling Project: Creating Indigenous Digital Pathways - Sam, Johanna; Schmeisser, Corly; Hare, Jan (KULA)

(untitled) (University of Victoria Libraries, 2021)
Background: Indigenous learners and community members are often excluded from online learning environments, as both consumers and producers of knowledge, resulting in an educational digital divide. Further, Indigenous knowledges represented through digital practices and online spaces risk misrepresentation and appropriation, which leads to stereotypes and deficit thinking about Indigenous people, their histories, and their current realities. There is a need for educational approaches that give space, voice, and agency to Indigenous people. Aim: This article is a reflection on a teaching enhancement project that weaved together local land-based learning, Indigenous storytelling, and digital media. Project Overview: Indigenous pre-service teachers created an open educational resource, the Grease Trail Digital Storytelling Project, to enhance the preservation and accessibility of Indigenous histories, stories, and memories embedded in local landscapes. Their approach to Indigenous digital storytelling uses the principles of respect, relevance, responsibility, and reciprocity to document and curate their digital storytelling practices and Indigenous knowledgetraditions. Discussion: The Grease Trail Digital Storytelling Project may serve as a helpful resource for those interested in learning how Indigenous digital storytelling could be approached for the preservation of Indigenous intellectual traditions that bring together land, story, and memory in online spaces and integrated as a tool for teaching and learning in school and community settings.